Ultrafast gigantic photo-response in (EDO-TTF)(2)PF6 initiated by 10-fs laser pulses - Itatani, J; Rini, M; Cavalleri, A; Onda, K; Ishikawa, T; Koshihara, S; Shao, X; Yamochi, H; Saito, G; Shoenlein, R (Optical Society of America, 2007)
We photo-excited a charge-ordered organic salt (EDO-TTF)(2)PF6 with sub- 10-fs optical pulses. The photo-induced metallic phase appeared within 80-fs after pumping, characterized by large changes in reflectivity (Delta R/R similar to 0.8) followed by strong coherent phonon modulation.